The Imaginary Geography of Hollywood Cinema 1960-2000 - Long, Christian B. (Intellect, 2017)
The Imaginary Geography of Hollywood Cinema 1960-2000 combines digital cartography with close readings of representative films to write a history of twentieth century Hollywood narrative cinema at the intersection of the geographies of narrative location, production, consumption and taste in the post-classical era, before the rise of digital cinema. This text reorients and redraws the boundaries of film history both literally and figuratively by cataloguing films' narrative locations on digital maps to examine where Hollywood locates its narratives over time.